Evaluation of information available on the internet regarding reverse total shoulder arthroplasty. (July 2019) - Houck, Darby A.; Kraeutler, Matthew J.; Belk, John W.; McCarty, Eric C.; Bravman, Jonathan T.
Background: Prior studies have analyzed the quality of information available on the Internet regarding common orthopaedic surgical procedures. The purpose of the present study was to evaluate the quality of information available for reverse total shoulder arthroplasty (rTSA). Methods: Websites were identified using the search term 'reverse total shoulder arthroplasty' and the first 50 websites from three separate search engines (Google, Yahoo, and Bing) were selected for evaluation of authorship and quality of information using the DISCERN instrument (www.discern.org.uk ). After disregarding duplicated or overlapping websites within and among search engines, 90 of the total 150 websites were evaluated. A one-way analysis of variance test was used to compare differences in DISCERN scores between three categories of authorship (academic, private, other). Results: The majority of the websites evaluated were authored by academic (43%) and private institutions (36%). These were the most credible sources, providing overall better quality and reliability than other sources. DISCERN reliable ( p  = 0.017) and overall scores ( p  = 0.020) were significantly higher for academic institutions compared to other websites. Conclusions: The information available on the Internet pertaining to reverse total shoulder arthroplasty is highly variable and provides moderate quality information about treatment choices with some limitations based on the DISCERN instrument.